Breast abnormalities in adolescents receiving antiretroviral therapy - Jackie L. Dunlop; Wiedaad Slemming; Kathryn Schnippel; Caroline Makura; Leon J. Levin; Sarah Rayne; Marnie Vujovic; Cynthia Firnhaber (AOSIS, 2019)
Background: Antiretrovirals, particularly efavirenz (EFV), have been shown to cause breast abnormalities in adults. Little is known about the prevalence of these adverse effects among adolescents receiving antiretroviral therapy (ART). Objectives: The aim of this article was to examine the extent of breast abnormalities in adolescents receiving ART and determine any clinical associations. Methods: A retrospective record review describing breast conditions in adolescents receiving ART at three facilities in Johannesburg was conducted. Patients aged 10-19 years, who presented from January to December 2014, were included in the study. Analyses were conducted to determine whether EFV was associated with increased breast conditions. Results: Of the 631 patient records reviewed, 37 (6%) had an abnormal breast event documented; with 24/37 (65%) being male patients. Patients with abnormal breast conditions were 1.5 years older than patients with normal breast development (p 0.0005). Forty-one abnormal breast events were observed in 37 patients, with 20 described as gynaecomastia or lipomastia (49%). Of the 37 patients, 44% (n = 19) had concurrent generalised lipodystrophy. Of those with an abnormal breast event, 71% of patients had CD4 counts 500 cells/µL and were virologically suppressed (n = 29). Those on EFV had a significantly higher prevalence of breast abnormalities compared to other regimens (p = 0.016). Conclusion: Of the studied patients, 6% had an abnormal breast condition. The use of EFV and increased age were associated with breast abnormalities in this population. Further research is needed to better understand the implications of this potential side effect.